2013
DOI: 10.1111/pace.12309
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Tachyarrhythmias Temporally Precede Fluid Accumulation in Implantable Device Patients

Abstract: Thoracic fluid accumulation, as indicated by decreasing intrathoracic impedance, was more likely to occur immediately after the onset of persistent AT/AF, especially in the presence of inadequate rate control. Likewise, the onset of persistent AT/AF was more likely following a decrease in intrathoracic impedance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This hypothesis is supported by the study from Andriulli et al who found a high probability of fluid index threshold crossing events, reflecting worsening HF, in the first month following the onset of AT/AF. The permanent AF patients were less likely to experience fluid index threshold crossing events 14 …”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis is supported by the study from Andriulli et al who found a high probability of fluid index threshold crossing events, reflecting worsening HF, in the first month following the onset of AT/AF. The permanent AF patients were less likely to experience fluid index threshold crossing events 14 …”
Section: Discussionmentioning
confidence: 97%
“…Neurohormonal activation, electrolyte disturbances, and myocardial ischemia during acute HF may also exert proarrhythmic influences in the myocardium [18]. OVFI values calculated from ITI trends have been validated to inversely correlate with pulmonary capillary wedge pressure and fluid balance and with changes in N-terminal pro-hormone brain natriuretic peptide [8,12]. Multiple studies have investigated the association between decreased ITI quantified by the OVFI and both AT/AF and VT/VF in patients with HFrEF [8,19].…”
Section: Discussionmentioning
confidence: 99%
“…OVFI values calculated from ITI trends have been validated to inversely correlate with pulmonary capillary wedge pressure and fluid balance and with changes in N-terminal pro-hormone brain natriuretic peptide [8,12]. Multiple studies have investigated the association between decreased ITI quantified by the OVFI and both AT/AF and VT/VF in patients with HFrEF [8,19]. A meta-analysis summarizing the published evidence of the association between OVFI and development of AT/AF and VT/VF reported a statistically significant association between increased OVFI and AT/AF and VT/VF onset in patients with HFrEF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations